ANALYSIS OF NOISE INTENSITYON WORK COMFORT AT PUBLIC FUEL FILLING STATION (SPBU) ZAMHUR BATOH BANDA ACEH IN 2025 - Nirwana Nirwana; Rahmadani Rahmadani (Getsempena Health Science Journal, 2026)
Noise is one of the physical environmental factors that can have negative impacts on comfort and occupational health. The Zamhur Batoh Gas Station (SPBU Zamhur Batoh) in Banda Aceh, located on the city’s main traffic route, has a high potential for noise exposure due to vehicle traffic and fuel dispensing operations. This study aims to analyze the effects of noise intensity, types of noise, and duration of noise exposure on work comfort among employees at SPBU Zamhur Batoh Banda Aceh in 2025 Methods: This study employed a descriptive analytic method with a cross-sectional approach. The population consisted of all 20 employees of SPBU Zamhur Batoh Banda Aceh, who were also taken as the study sample. Noise intensity data were collected through measurements using a Sound Level Meter (SLM) at five measurement points during five different time sessions on both workdays and holidays. Data on types of noise, duration of exposure, and work comfort were obtained through questionnaires. Results: The results showed that 45% of respondents worked under noise intensity levels exceeding the Threshold Limit Value (TLV) of >85 dBA, and all respondents in this category reported experiencing discomfort at work. The dominant types of noise were intermittent noise (45%), impulsive noise (20%), repetitive impulsive noise (10%), and continuous noise (25%). A total of 80% of respondents were exposed to noise for more than 40 hours per week, and 87.5% of them reported discomfort during work. Conclusion: Statistical analysis indicated a significant relationship between noise intensity (p=0.038) and duration of exposure (p=0.032) with work comfort, while no significant relationship was found between types of noise and work comfort (p=0.551).